Improving the Impact Resistance through Annealing in PLA 3D Printed Parts - Zisopol, Dragos Gabriel; Portoaca, Alexandra Ileana; Tanase, Maria (Engineering, Technology & Applied Science Research, 2023)
This study conducts an experimental exploration and thorough analysis of the influence of annealing on the impact resistance of PLA 3D-printed components. The investigation extends its scope to encompass the influence of printing parameters, specifically layer thickness and infill percentage. The research highlights that the impact resistance of annealed 3D printed PLA components is predominantly influenced by the infill percentage, with the highest impact energy observed at a full 100% infill. It is noticeable that the application of annealing post-processing heat treatment results in a remarkable, up to threefold, increase of the impact energy highlighting its potential efficacy as a viable technique for enhancing the mechanical integrity of PLA 3D printed products. Consequently, this study establishes annealing as a promising methodology, particularly for PLA 3D printing applications that encounter significant mechanical loads.